Mining Permits and Environmental Justice in Indonesia: Imam Al-Mawardi's Perspective on the Decision of the Semarang Administrative Court No. 68/G/Pu/2021/PTUN.SMG - Aulia Luthfi Ramadhan; Mustapa Khamal Rokan (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2025)
This study aims to analyze the dynamics of mining permits in Indonesia through a case study of the Semarang Administrative Court Decision No. 68/G/Pu/2021/PTUN.SMG, with a particular focus on environmental justice for the residents of Wadas Village from the perspective of Imam Al-Mawardi's thought. The research employs a normative juridical method with a qualitative approach, examining legal documents, court rulings, mining regulations, and Islamic literature related to the concept of justice. The findings reveal that the court's consideration primarily emphasizes administrative and procedural legality, while neglecting the principle of substantive justice, which, according to Al-Mawardi, centers on the protection of community rights, public welfare (maslahah), and the prevention of environmental damage. These findings highlight a disparity between national development interests and the rights of local communities. Accordingly, the study recommends a reform of mining permit policies to ensure greater participation and fairness, as well as the integration of the principle of al-‘adalah (justice) into legal decision-making and public policy processes in Indonesia.